Structural Adjustment Policy Experiments: The Use of Philippine CGE Models - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1994)
This paper reviews the general structure of the following general computable general equilibrium (CGE): the APEX model, Habito's second version of the PhilCGE model, Cororaton's CGE model and Bautista's first CGE model. These models are chosen as they represent the range of recently constructed CGE models of the Philippine economy. They also represent two schools of thought in CGE modeling: the well defined neoclassical, Walrasian, general equilibrium school where the market-clearing variable is the price, and the non-Walrasian or structuralist school where the market-clearing variable is quantity. Actual simulations using these models are conducted.
Keywords: 330; tariff reduction; stabilization program; income distribution; computable general equilibrium (CGE); agriculture sector; input-output framework; devaluation; APEX model; export demand elasticity; balance of payments